Evaluation of obesity and its risk factors among rural adults in Tamil Nadu, India - R. C., Karthik; S., Gopalakrishnan (International Journal Of Community Medicine And Public Health, 2018)
Background: Obesity is a largely emerging multi-factorial non-communicable disease, which is caused due to accumulation of fat cells either by an increase in the size or number. World over, obesity has been proven to be the leading cause for several non-communicable diseases like diabetes, hypertension, cancer, etc. This study was done to evaluate the prevalence and risk factors of obesity in a rural population of Tamil Nadu. Methods: This cross sectional study was carried out among 600 adults residing in Sripuram, a rural field practice area of our medical college. Data was collected by systematic random sampling method, using a structured questionnaire, to assess the socio-demographic characteristics, anthropometry and physical examination findings. Body Mass Index was calculated and classified as per WHO classification for Asians. SPSS Software Version 17 was used to analyze the data. Results: Among the 600 total study subjects, 317 subjects (52.8%) were males and 283 subjects (47.2%) were females. The age distribution among the study population ranged between 20-60 years. Prevalence of overweight (BMI>23) was 25.3% and prevalence of obesity (BMI>25) was 25.5%. About 11.5% of the study subjects were underweight (BMI>18.5) and 37.7% of the study population had normal weight. Sibling obesity and presence of thyroid disorders were significantly associated with the risk of overweight and obesity. Conclusions: This study highlights the need for periodic screening to detect obesity at its incipient stages. It is pertinent that awareness is created periodically to modify the diet and lifestyle risk factors in order to prevent further complications of obesity.